Motivasi Peternak Sapi Bali dalam Menggunakan Sistem Bagi Hasil Di Desa Bambangan Kecamatan Malunda Kabupaten Majene - Astati, Astati; Alwi, Muhammad Alwi; Khaifah Asgaf; Rusny, Rusny; Susanti, Handayani Indah (Anoa: Journal of Animal Husbandry, 2024)
This study aims to determine the characteristics of Balinese cattle breeders in using the profit-sharing system in Bambangan Village, Malunda District, Majene Regency and the factors that affect the motivation of Balinese cattle farmers in using the profit-sharing system in Bambangan Village, Malunda District, Majene Regency. This research was carried out from October to November 2023, in Bambangan Village, Malunda District, Majene Regency. The number of population in this study is 100 breeders who are spread in the location, so sampling is carried out using the slovin formula with an error rate of 10%, the sample obtained is 50 breeders. This type of research is quantitative descriptive, namely research that explains capital limitations, risk sharing, knowledge and access to the market in Bambangan Village, Malunda District, Majene Regency. Data collection using a questionnaire applied the Likert Scale. The data analysis used was Multiple Linear Regression. The results of the study showed that the characteristics of Balinese cattle breeders in Bambangan Village, Malunda Kabuaten Majene District, including age, gender, education level, livestock experience and the number of livestock ownership as a whole affect the business carried out by the breeder. Based on multiple linear regression analysis, the motivation of Balinese cattle farmers in using the profit-sharing system in Bambangan Village, Malunda District, Majene Regency was influenced by 3 factors, namely capital limitation (X1), significance value 0.000 < 0.05 T, count 6,901, risk division (X2), significance value 0.046 > 0.05 T, count 2,057 and knowledge (X3) significance value 0.002 < 0.05 T count 3,292. Meanwhile, access to the market (X4) has a significance value of 0.078> 0.05 T calculated -1,801 has no effect (real) on the motivation of farmers who share profits.